Can nature conservation and wood production be reconciled in managed forests? A review of driving factors for integrated forest management in Europe. (15th August 2020) - Aggestam, F.; Konczal, A.; Sotirov, M.; Wallin, I.; Paillet, Y.; Spinelli, R.; Lindner, M.; Derks, J.; Hanewinkel, M.; Winkel, G.
Abstract: Integrated forest management (IFM) can help reconcile critical trade-offs between goals in forest management, such as nature conservation and biomass production. The challenge of IFM is dealing with these trade-offs at the level of practical forest management, such as striving for compromises between biomass extraction and habitat retention. This paper reviews some of the driving factors that influence the integration of nature conservation into forest management. The review was conducted in three steps – a literature review, an expert workshop and an expert-based cooperative analysis. Of 38 driving factors identified, three were prioritised by more of the participants than any of the others: two are socio-cultural factors, identity (how people identify with forest) as well as outreach and education, and one is economic – competitiveness in forest value chains. These driving factors correspond to what are considered in the literature as enablers for IFM. The results reveal that targeted, group-oriented, adaptive and innovative policy designs are needed to integrate nature conservation into forest management. Further, the results reveal that a " one-size-fits-all " governance approach would be ineffective, implying that policy instruments need to consider contextually specific driving factors. Understanding the main driving factors and their overall directions can help to better manage trade-offs between biodiversity conservation and biomass production in European forests. Graphical abstract: Image 1 Highlights: Integrated Forest Management may help to reconcile critical trade-offs in forest management. 38 driving factors identified as important for integrating nature conservation into forest management. Several driving factors correspond to what can be considered as enablers of Integrated Forest Management. Policy need to account for contextually specific driving factors to integrate nature conservation. Integrative approaches demonstrate the need for targeted, group-oriented and adaptive policy designs.